Relating Ken Wilbers Consciousness Development Model With Psychotherapy - Hanna Rasel Scherler (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
In this article, the relation between consciousness development, psychopathology and psychotherapy is discussed in the framework of a concept called saturated contact, and examples from cognitive therapy approach are offered. The article is structured in the framework of the concept of saturated contact between therapist and client. Saturated contact takes place when the encounter satisfies each partys need. The quality of the encounter is a reflection of the quality of each partys encounter with himself. Contact contains the functions of integrating/differentiating and including/transcending. These functions are to be found throughout consciousness development in the persons contact with physical, emotional and cognitive structures respectively. When psychotherapy is defined as defects in the integrating/differentiating and including/transcending functions, the need becomes the reparation of the defects. Reparation takes place when the persons contact with those structures that he denies, represses or transforms due to the derailment in the consciousness development process is supported. Saturated contact in the therapist client relation is experienced when the therapist meets the client where he is in the consciousness spectrum and when the therapist structures his intervention and uses the techniques in accordance with the clients need. Where the therapist is located in the spectrum of consciousness also plays an important role in the experience of saturated contact. In therapy realityis defined by the party who contains the structure that is least comprehensive and most shallow. Therefore the therapists consciousness level must include and transcend that of the client. [JCBPR 2018; 7(1.000): 42-50]